Pengaruh Pupuk NPK dan ZPT Air Kelapa Terhadap Hasil Tanaman Pakcoy (Brassica rapa L.) - Sintia, Ema; Sa'diyah, Halimatus (Universitas Nusa Bangsa, 2024)
Pakchoy or Brassica rapa L. is called a plant with a distinctive taste and high nutritional content. Pakchoy productivity is still experiencing a decline and is inversely proportional to the increase in demand for pakchoy products. The research was carried out with the aim of finding out the effect of applying NPK fertilizer and coconut water PGR on the yield of pak choy plants. This research used factorial completely randomized design with 2 factors namely NPK fertilizer doses (0 kg/ha; 150 kg/ha; 300 kg/ha; 450 kg/ha) and coconut water PGR concentrations (0%; 25%; 50%; 75 %). The significant interaction effect is in the leaf chlorophyll variable with the highest value at the NPK fertilizer dose of 300 kg/ha and the PGR concentration of 0% coconut water was 43.2 per mm2. The significant interaction effect was also shown in the dry weight variable with the highest value at the NPK fertilizer dose of 450 kg/ha and the PGR concentration of 0% coconut water of 14.5 g. NPK fertilizer has significant and very significant effect on the research variables with the best treatment of 450 kg/ha. The PGR of coconut water treatment had no significant effect on the research variables, except for the variable number of leaves with the highest average at a concentration of 0%. Pakcoy atau Brassica rapa L. disebut sebagai tanaman dengan cita rasa yang khas dan kandungan nutrisi tinggi. Produktivitas pakcoy masih mengalami penurunan dan berbanding terbalik dengan peningkatan permintaan produk pakcoy. Penelitian dilakukam dengan tujuan untuk mengetahui pengaruh aplikasi pupuk NPK dan ZPT air kelapa terhadap hasil tanaman pakcoy. Penelitian ini menggunakan rancangan faktorial RAL dengan 2 faktor berupa dosis pupuk NPK (0 kg/ha; 150 kg/ha; 300 kg/ha; 450 kg/ha) dan konsentrasi ZPT air kelapa (0%; 25%; 50%; 75%). Pengaruh interaksi nyata pada variabel klorofil daun dengan nilai tertinggi pada dosis pupuk NPK 300 kg/ha dan konsentrasi ZPT air kelapa 0% sebesar 43,2 per mm2. Pengaruh interaksi nyata juga ditunjukkan pada variabel berat kering dengan nilai tertinggi pada dosis pupuk NPK 450 kg/ha dan konsentrasi ZPT air kelapa 0% sebesar 14,5 g. Pupuk NPK berpengaruh nyata dan sangat nyata terhadap variabel penelitian dengan perlakuan terbaik 450 kg/ha. Perlakuan ZPT air kelapa tidak berpengaruh nyata terhadap variabel penelitian, kecuali terhadap variabel jumlah daun dengan rata-rata tertinggi pada konsentrasi 0%.